Kesehatan Mental Dalam Kajian Semiotika Charles Sanders Pierce Pada Film “Ngeri-ngeri Sedap” - Risa Aulia; Fakhrur Rozi; Ismail (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2023)
This study explains about film representation which is a part of mass communication media. This research adopts a family film with elements of custom and culture, which is entitled the film “Ngeri-Ngeri Sedap”. This study aims to draw a message contained in a film in the form of mental health in the family and public sphere. This study uses a qualitative approach with the Charles Sanders Pierce analysis method which has three parts and is referred to as the triangle theory, namely sign, object, and interpretant. The primary data source in this study is the result of video recordings and secondary data sources derived from theoretical studies of journals and books. Data collection techniques using observation and documentation methods through image capture. The results of this study show that mental health provides an educational message related to a person's psychological condition within the scope of the family or community. Coverage in mental health is divided into three parts including stress, inability to adapt, and decision making which is represented psychologically and physically